Detection of two cryptic taxa in Meristogenys amoropalamus (Amphibia, Ranidae) through nuclear and mitochondrial DNA analyses - Shimada, Tomohiko; Matsui, Masafumi; Yambun, Paul; Lakim, Maklarin; Mohamed, Maryati (Zootaxa, 2008)
We identified three distinct sympatric lineages of frogs among specimens previously considered a single species (Meris- togenys amoropalamus Matsui), based on 909 bp of mitochondrial DNA (12S rRNA and cytochrome b). To seek evidence of reproductive isolation between these lineages, we first analyzed a 249-bp fragment of the nuclear proopiomelanocortin (POMC) gene and found five haplotypes, of which two were limited to lineage 1 and three belonged to lineages 3 and 4. In a subsequent phylogenetic analysis of a 1313-bp fragment of nuclear POMC, Rag-1, and rhodopsin, lineage 1 was again distinct, while lineages 3 and 4 could not be differentiated. The results of the nuclear gene analyses suggest that lineage 1 is strongly isolated reproductively from lineages 3 and 4, which are not isolated from each other. This conclusion conforms to groupings based on larval morphology. These results indicate that frogs morphologically identified as M. amoropalamus should be split into two sympatric species, one of which contains two mitochondrial lineages that have presumably been retained via deep coalescence.